Pemanfaatan Animasi 2D sebagai Media Pembelajaran Literasi Digital Ramah Anak di Era Society 5.0 - Deli; Nelson Handoko; Jimmy Pratama (MULTINETICS, 2025)
This study aims to develop 2D animation as a child-friendly digital literacy learning medium in the Society 5.0 era, focusing on three main aspects, namely internet safety, digital ethics, and digital creativity. The media development was carried out using the Multimedia Development Life Cycle (MDLC) model through six stages: concept, design, material collecting, assembly, testing, and distribution, which were implemented using Adobe Illustrator, Adobe After Effects, and Adobe Premiere Pro software. The evaluation was conducted using a qualitative approach through interviews with 46 respondents consisting of teachers and students in Batam City to assess the visual and audio quality, clarity of material, relevance of content, and effectiveness of animation in supporting digital literacy understanding. The results of the study showed that the majority of respondents rated the quality of the images, characters, and sound as very good and attractive, the presentation of the material was easy to understand, and the information conveyed was accurate and reliable. In addition, 2D animation was considered capable of increasing knowledge about the safe, ethical, and creative use of digital technology, while also attracting children's interest in learning. These findings indicate that 2D animation has strong potential as a child-friendly digital literacy learning medium that is relevant to the context of Society 5.0, and can be used as a model for the development of similar media at other levels and in other educational environments.